Feasibility, safety, and efficacy of circumferential spine stereotactic body radiotherapy - Dibs, Khaled; Palmer, Joshua D.; Prasad, Rahul N.; Olausson, Alexander; Bourekas, Eric C.; Boulter, Daniel; Ayan, Ahmet S.; Cochran, Eric; Marras, William S.; Mageswaran, Prasath; Thomas, Evan; Grecula, John; et al. (Frontiers in Oncology, 2022)
Background: With advances in systemic therapy translating to improved survival in metastatic malignancies, spine metastases have become an increasingly common source of morbidity. Achieving durable local control (LC) for patients with circumferential epidural disease can be particularly challenging. Circumferential stereotactic body radiotherapy (SBRT) may offer improved LC for circumferential vertebral and/or epidural metastatic spinal disease, but prospective (and retrospective) data are extremely limited. We sought to evaluate the feasibility, toxicity, and cancer control outcomes with this novel approach to circumferential spinal disease. Methods: We retrospectively identified all circumferential SBRT courses delivered between 2013-2019 at a tertiary care institution for post-operative or intact spine metastases. Radiotherapy was delivered to 14-27.5 Gy in 1-5 fractions. Feasibility was assessed by determining the proportion of plans for which ≥95% planning target volume (PTV) was coverable by ≥95% prescription dose. The primary endpoint was 1-year LC. Factors associated with increased likelihood of local failure (LF) were explored. Acute and chronic toxicity were assessed. Detailed dosimetric data was collected. Results: 58 patients receiving 64 circumferential SBRT courses were identified (median age – 61, KPS≥70, 57% male). With a median follow-up of 15 months, the 12-month rate of LF was 15% (8 events). 5 and 3 recurrences were in the epidural space and bone, respectively. On multivariate analysis, increased PTV and uncontrolled systemic disease were significantly associated with increased likelihood of LF. ≥95% PTV was covered by ≥95% prescription dose in 94% of cases. The rate of new or progressive vertebral compression fracture was 8%. There were no myelitis events or any grade 3+ acute or late toxicities. Conclusions: For patients with circumferential disease, circumferential spine SBRT is feasible and may offer excellent LC without significant toxicity. Prospective evaluation of this approach is warranted.